Health Informatics in the 21st Century: The Role of Data in Advancing Healthcare - Mohammed Javeedullah; Shah Zeb (CV. Shofanah Media Berkah, 2023)
Health informatics is changing healthcare by joining technology, data study and digital solutions to support patient care, streamline working methods and fight public health problems. Better ways of care coordination and decision-making are possible now thanks to Electronic Health Records (EHRs), Health Information Exchange (HIE) and interoperability. Artificial Intelligence (AI), Machine Learning (ML) and big data analytics are used to optimize healthcare by enabling customized treatment and making predictions about health problems. Even so, worries about data privacy, cybersecurity and healthcare professionals not wanting to change still cause problems. Trust and fairness in health informatics rely heavily on following ethical and legal rules such as getting patient permission and staying within the limits set by regulators. Health informatics is playing a larger part in public health by making disease surveillance and managing the health of populations more effective. For health informatics to achieve its maximum effects in changing healthcare, it must address these issues.